Designing UI and UX Design in GenApp Application Using Design Thinking Method - Rifda Falsa Salsabila; Ayung Candra Padmasari (IJOEM: Indonesian Journal of E-learning and Multimedia, 2024)
This research aims to create an ARBook learning application design for high school students on genetic material. Today's growing technology has affected various fields, one of which is education. Generation Z is a generation that understands and is literate in technology. High school students born in Generation Z have characteristics that tend to like technology, are smart, open, and like to express themselves. To attract students' interest in learning, there needs to be media used by utilizing technology. It is necessary to understand the characteristics of students when making learning media design. The method used in this research is the design thinking method, which has five stages: emphasize, define, ideate, prototype, and test. This research produces an ARBook GenApp application design that suits the characteristics of Generation Z students. The test results from the student response trial obtained good results of 89.17%, which were included in the very feasible criteria.